2016
DOI: 10.4139/sfj.67.8
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Surface Modification Process by Fine Particle Peening

Abstract: Ti/Al MM particle Aluminum melts heating by combustion synthesis reaction. Ti-Al intermetallic compound layer 図 9 AIH-FPP による Ti-Al 金属間化合物層創成メカニズム SEM image Fe mapping Ti mapping Al mapping 100μm 300 μm 図 8 Ti:Al = 1:3 MM 粒子を用いた処理試験片の断面分析

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Furthermore, a new surface treatment, wide peening cleaning (WPC), was developed to improve fatigue strength of steels using shot peening and sandblast technologies. This process was developed by FUJI KIHAN Co., Ltd [2]. It was reported that WPC was better than shot peening because it increased compressive residual stress [3].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a new surface treatment, wide peening cleaning (WPC), was developed to improve fatigue strength of steels using shot peening and sandblast technologies. This process was developed by FUJI KIHAN Co., Ltd [2]. It was reported that WPC was better than shot peening because it increased compressive residual stress [3].…”
Section: Introductionmentioning
confidence: 99%